Analysis of Project Time Acceleration Using The Crashing Method in The Rehabilitation Project of SMPN 2 Pasongsongan, Sumenep District - K., Moh Ali Lutfi M.; Witjaksana, Budi; Purnama, Jaka (Pusat Publikasi Nusantara, 2025)
Delays in construction projects often result in increased costs and inefficiencies, which can negatively impact project management and resource allocation. To address these issues, this study analyzes project duration acceleration using the Crashing Method by incorporating overtime work hours and additional workforce into the rehabilitation project of SMPN 2 Pasongsongan, Sumenep Regency. This research aims to determine the extent of time reduction achievable when implementing a 3-hour overtime strategy and increasing the workforce simultaneously. Utilizing Microsoft Project 2016, the study compares the original 150-day schedule with an accelerated version using the Crashing Method. The results indicate that the project duration can be reduced to 140 days, saving 10 days. However, this acceleration incurs an additional cost of IDR 21,566,522, primarily due to labor expenses and extended work hours. The study further examines the trade-offs between time efficiency and cost implications, highlighting the importance of effective resource management in construction projects. Findings suggest that the Crashing Method is an effective strategy for project acceleration, provided that cost-benefit analysis, workforce efficiency, and resource availability are carefully considered. The study also emphasizes that proper coordination among project stakeholders, optimized scheduling, and proactive risk assessment are critical for ensuring that acceleration does not compromise work quality or safety standards. By offering insights into the practical application of the Crashing Method, this research serves as a valuable reference for project managers and construction planners seeking to improve time efficiency while maintaining budget control in infrastructure projects.